“Enjoylish Adventure” Learning Media Based on Construct 2 Improves English Learning Outcomes of Fourth Grade Elementary School - Rohman Sujarwo, Fatkhur; Andaryani, Eka Titi (Jurnal Pendidikan dan Pengajaran, 2024)
Teachers need help creating learning media for English, resulting in low English learning outcomes. Based on this, this research aims to develop "Enjoylish Adventure" Learning Media Based on Construct 2 for English language learning for fourth-grade elementary schools. This type of research is designed using the ADDIE model. The subjects of this research are learning media experts and learning content experts. The test subjects for this research were 25 students. The methods used to collect data are interviews, questionnaires, observations and tests. Data collection instruments use questionnaire sheets and test questions. Data analysis techniques use data analysis techniques in the form of qualitative, quantitative and inferential statistics. The results of the research, namely the assessment given by English language material experts, obtained a score of 94% (very valid) and learning media experts, namely 90% (very valid). The results of the teacher's response obtained a percentage score of 100% (very practical), and the student response was 87.9% (very practical). The t-test results show differences in student learning outcomes after using enjoylish adventure media. The results of the n-gain test also show that the small group got the high category and the large group got the sufficient category. Based on the results of data analysis, it can be concluded that the "Enjoylish Adventure" Learning Media Based on Construct 2 is effectively used to improve student learning outcomes.